A techno-religious framework to scaffold spiritual intelligence among students / Salimah Mokhtar - Salimah , Mokhtar (2017)
Spirituality is an essential core of a person and the basis of life. Negligence of spiritual dimension has raised many problems particularly relevant to the degradation of moral values among students. Lack of spirituality is the root cause of the chaos and crises in the contemporary world. Spirituality is vital in student’s development and therefore higher education should honour this dimension in the pursuit of knowledge in order to understand the absolute truth. This research explores the use of information technology (IT) to cultivate university students’ spiritual development. The perspectives of information technology, holistic education and spiritual and religious aspect of human development influenced the undertaken research work. The education component is the study context; the religious and spiritual element is the study content; and information technology is the beneficial support tool for spiritual engagement among undergraduate Muslim students. This study adopts design research methodology, which goes through phases of awareness of problem, suggestion, development, evaluation and conclusion. In order to nurture student’s spirituality, a techno-religious framework is proposed to guide the building of a spiritual learning system called Spiritual Reflective System (SRS). Provision of guidance, resources and learning environment that values spirituality is via an informal learning channel. The learning process is through face-to-face interaction with a teacher and SRS support. A focus group survey and discussion are the method of data collection in evaluating the meaningfulness of SRS. Four main criteria of evaluation used are the feel, awareness, consciousness and mindfulness. The system had created the feel in the participants that mostly came from the audio and video tazkirah, words of advice, online Quran recitation, Hadith and Islamic poster message. Knowledge gained through SRS made them realize the real purpose, vision and mission of the worldly life and triggered their mind to think about the existential questions. The chance of knowing these implicit stuffs in an explicit way has created awareness in them. They admitted that they are conscious concerning the things they know very well except that they do not practice. None of them claimed to be mindful of Allah at all times. The participants agreed that the SRS support the National Education Philosophy. Overall results confirmed that participants of the Spiritual Reflective System find the system useful and went through a positive learning experience in using the system. However to gain spiritual intelligence, students need more than self-learning, this system is just an assistance in the first step to progress towards spiritual intelligence journey.